Graphene oxide - silica composite aerogels as pharmaceutical nanocarriers - ÇALIŞKAN SALİHİ, ELİF; BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2022)
After the isolation of graphene at the beginning of the 21st century, studies on the production of different materials gained momentum and the synthesis of new generation materials including graphene-based structure became possible. In addition to having unique physicochemical properties, graphene can be produced and modified in a wide variety of ways according to the requirements of different applications. Graphene has great potential to be used in drug delivery systems due to its large surface area and high biocompatibility [1]. Aerogels, on the other hand, are the most porous materials known, and they stand out with their much larger surface areas compared to other nanomaterials. Large surface areas and ultra-porous structures of aerogels are great advantages for drug carrying capacity, so aerogels constitute an important potential for targeted drug delivery applications [2]. Within the scope of this work, graphene oxide-silica composite aerogel nanostructures were produced based on the incorporation of the unique properties of graphene into the ultra-porous structure of aerogels using Sol-gel and ambient pressure drying method, which is advantageous in terms of time and cost. An important step in material production is the physicochemical characterization of these materials. Common and advanced techniques such as electron microscopy and XRay diffraction analysis were used for the characterization of materials. Biocompatibility and drug loading performance of the clear and in-situ functionalized aerogels were revealed. The biocompatibility of the nanocarriers were tested using cell viability assay and drug loading tests were done by using curcumin. Functionalization done with sodium dodecyl sulphate, polyvinylpyrrolidone and ethylenediaminetetraacetic acid affected the cytotoxicity and entrapment efficiency of the composite aerogels significantly. Sodium dodecyl sulfate functionalized aerogel showed the highest rate of cellular proliferation while all the samples presented high cellular proliferation rates in a dose dependent manner. Entrapment efficiency of ethylenediaminetetraacetic acid functionalized aerogel (59%) was higher than the other three samples (between 20%-50%) which is a crucial parameter to evaluate the nanocarriers. According to these promising results, we consider this study as the first step in the development of targeted new aerogel based carrier platforms for cancer therapy
Keywords: graphene; aerogel; nanocarrier; curcumin; cancer therapy